Water History - Ertsen, Maurits W.; Arnold, Ellen; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The general purpose of the Water History is to encourage, promote, and foster historical understanding of the relationship between water and humankind. As water has influenced the development of human communities throughout the world, the study of water contributes to our understanding of economic, political, social, and environmental history, the history of science, medicine, technology, environmental sciences, and geography. To reflect the wide range of academic disciplines involved in the growing field of water history, Water History seeks to foster cross-disciplinary discussion of ideas, methods, and experience so as to illuminate the complex processes that have shaped water resource use and thus reveal interrelated historical contingencies and precedents. The management of the world$1 (Bs water supplies remains of critical concern to scholars, policymakers, and resource managers; as such, deepening our understanding of how past human societies used and related to water informs current debates on water management. The history of water use can be a deeply political issue. Conflicts over the control and use of water have varied both historically and geographically, often crossing cultural, geographical, and institutional boundaries. In recognition of the complexity and sometimes contradictory aims and ideologies of those controlling water resources, Water History will provide a forum for peer-reviewed research in the field of water history and management. The journal will foster effective links between scholars engaged in water history research in the humanities and social sciences as well as the natural and applied sciences.s
Keywords: Water; History; Hydrogeology; Civil engineering; Water pollution; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Water, general; Civil Engineering; Hydrogeology; History, general